1996
DOI: 10.1007/bf01922412
|View full text |Cite
|
Sign up to set email alerts
|

Excess bioavailability of zinc may cause obesity in humans

Abstract: The body weight or body weight/height ratio exhibits a positive linear correlation to hair zinc (Zn) concentration which is more strongly positive in men than in women. The obese of both sexes possess higher Zn concentrations in their hair than those with normal body weight/height. The degree of obesity increases with the increase in the hair Zn concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 9 publications
2
12
1
Order By: Relevance
“…Further, increased Zn concentrations in the hair and nails in Group D M (middle-aged diabetics) and Group D+ OA (diabetics with osteoarthritis) also coincide well with respect to their increased body weights (Tables 1, 3, 4; Figs. 1a and 2a) because it is already reported in ours and other previous epidemiological studies where a positive relationship between Zn concentrations in hair with obesity, diabetics, and myocardial infarction but an inverse correlation with copper concentrations in hard tissues, such as hair and nails, were observed that support the present findings [21,[62][63][64]. Increase and decrease in hair and nail Zn levels in Groups OA and RA patients were reported due to the involvement of more cytokines, as RA is a chronic inflammatory disease.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Further, increased Zn concentrations in the hair and nails in Group D M (middle-aged diabetics) and Group D+ OA (diabetics with osteoarthritis) also coincide well with respect to their increased body weights (Tables 1, 3, 4; Figs. 1a and 2a) because it is already reported in ours and other previous epidemiological studies where a positive relationship between Zn concentrations in hair with obesity, diabetics, and myocardial infarction but an inverse correlation with copper concentrations in hard tissues, such as hair and nails, were observed that support the present findings [21,[62][63][64]. Increase and decrease in hair and nail Zn levels in Groups OA and RA patients were reported due to the involvement of more cytokines, as RA is a chronic inflammatory disease.…”
Section: Discussionsupporting
confidence: 93%
“…Recent data on Zn levels estimated in cereals and other food stuffs was also found to be high. The higher level of Zn in tissues of overweight and obese women than those with body mass index of 25 kg/m 2 observed in Indians, more so in Punjabis [62,63], is on account of high Zn in food [72] due to the liberal use of Zn as ZnSO 4 as a micronutrient in where in spite of hyperzincuria, the diabetic patients have not appeared to be Zn deficient [73]. This is further evident by elevated Zn concentration in serum, urine, and mononuclear cell in diabetic patients after high dose Zn supplementation, which has a greater ramification in diabetes [71].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A second factor is the sedentary lifestyle resulted in higher body mass index that was associated with its higher prevalence in the Chandigarh population [73] because total body fat had increased in the Chandigarh population as more than 73.70% population is engaged in light physical activity [72]. This increase in body weights in the Chandigarh population has also been reported to link with excessive dietary Zn, as its increase in diet than the recommended dietary allowance was evaluated to increase the body fat in rats, and higher Zn levels were observed in nail, hairs, and urine in obese than in normal subjects in the Chandigarh population according to previous studies [64,74,75].…”
Section: Discussionmentioning
confidence: 69%
“…5 Trace element status in obesity Consistent with some previous reports, we found lower serum zinc concentrations 16,43--45 and higher serum copper 16,46,47 and caeruloplasmin concentrations 16,48 in obese compared with non-obese subjects. However, Gjorup et al 49 reported no signi¢cant di¡erences of serum zinc concentrations between obese and non-obese subjects, and Yakinci et al 47 and Taneja et al 50 found that serum zinc concentrations in obese children were signi¢cantly higher than the control group.…”
Section: Effects Of Smoking On Trace Element Statusmentioning
confidence: 98%